Economic policy and the great stagflation - Blinder, Alan S. (New York : Academic Press, 1979)
This is a book both about national policy and about economics as a policy-oriented science.
Includes index.
Includes bibliographical references: p. 219-223.
ne 17/05/2018
Loans
Keywords: Inflation (Finance) and Unemployment; Econometrics; United States